PEMETAAN KERENTANAN AIRTANAH DI KECAMATAN GAMPING, KABUPATEN SLEMAN, PROPINSI DAERAH ISTIMEWA YOGYAKARTA - , SANGKA ARYA W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
about Sleman Regency Regulation No. 12 2012 Sleman Regency Spatial Planning 2011-2031 stated that Gamping District will be developed into a mediumsized industrial zones and urban residential areas with high population density. To determine the accuracy of the spatial planning according hydrogeology aspect, Groundwater contamination vulnerability mapping is necessary to be done. The results of the spatial planning and groundwater vulnerability evaluation are useful as a basis for decision making in the government about land use and groundwater protection. The first stage of groundwater pollution vulnerability mapping are hydrogeology mapping to determine the depth of groundwater and lithology unsaturated zone, groundwater sampling and collection of secondary data like rainfall and annual surface temperatures that are used to estimate the amount of groundwater recharge. Laboratory tests such as grain size analysis is performed to classify lithology of the unsaturated zone and nitrate analysis test to determine nitrate content in groundwater samples. Field observations results show that the thickness of unsaturated zone water is 1 to 12 m, lithology unsaturated zone is dominated by sand and average groundwater recharge value is 338.4 mm / year. Groundwater vulnerability maps is obtained by implementing groundwater depth, unsaturated zone lithology and groundwater recharge using Simple Vertical Vulnerability method. Groundwater vulnerability map is validated by comparing the class of contaminants, land use and nitrate content in groundwater in each class. The results showed that Gamping District consists of high groundwater vulnerability zone ( final score of protective effectiveness of the unsaturated zone is 19 to 24 ) and very high groundwater vulnerability zone ( final score of protective effectiveness of the unsaturated zone is 25 to 30 ), nitrate content in groundwater are generally still below 10 mg / L, the highest nitrate content is located on densely populated area land use. This is proved that the pollution of groundwater is determined by the interaction between land use as a source of groundwater contaminants and groundwater vulnerability.